Ni porphyrins and N-confused porphyrin: electronic structure studied by X-ray absorption - SENGE, MATHIAS (My University, 2009)
Due to their unique properties transition metal porphyrins are widely used in many technological applications such as sensors, solar cells, nonlinear optics and nanomaterials [1]. During the last decade the coordination properties and conformational flexibility of porphyrins were heavily exploited in a search of prospective isomers able to deliver better functionality in specific technological applications [1]. One such important class of porphyrins is the nitrogen-confused porphyrins (NCPs), which are novel and prospective materials with improved properties for use as acid catalysts and anion/cation sensors [2]. These porphyrin isomers differ greatly from the parent porphyrins, particularly in their chemical structure and their physical and coordination properties. The multivalent nature of NCPs as a metal ligand provides a potential strategy for stabilising and studying higher or atypical oxidation states of metals, e.g. Ni(I), Ni(III), Cu(III), Ag(III), or unusual coordination geometries [2]. In addition, the outer nitrogen or carbon atoms of the inverted pyrrole ring can be directly connected resulting in oligomeric porphyrin arrays with interesting applications. Using NCPs in such molecular arrays provides new modes of linking single molecules and different coordination properties of the resulting oligomers [2]. In order to realize their full potential a detailed knowledge of the electronic structure and chemical bonding in porphyrins is required. Such information can be obtained with x-ray absorption spectroscopy (XAS).
PUBLISHED
Keywords: porphyrins; Nanoscience & Materials